Rheological properties and thermal conductivity of water-based drilling fluid containing SiO2 and Al2O3 nanoparticles - Kalhori, Nahid; Mousavi-Kamazani, Mehdi; Hormozi, Faramarz (Journal of Composites and Compounds, 2023)
In this research, enhanced WBMs (water-based muds) was prepared by using SiO2 and Al2O3 nanofluids (size 15-20 nm) in aqueous solution of bentonite and investigated on thermal conductivity, filtration and rheological properties at three temperatures of 27, 50, and 80 °C. Nanofluids were prepared in different concentrations of 0.01, 0.03, 0.05, 0.1, 0.5, and 1 wt% in base fluid. Experimental data with flow curves for different nano water-based drilling fluid (NWBDF) are fitted to rheological drilling fluid models (Herschel-Bulkley, Bingham plastic, and power law models). According to the results, NWBDF follow Herschel Bulkley's model for rheological behavior. All samples exhibit shear-thinning behavior because the shear rate decreases as the apparent viscosity increases. After adding 1 wt% of SiO2 nanoparticles, the plastic viscosity (PV) increased to 14 ± 0.02 cP. Comparing the permeability of clay cakes according to Darcy's law showed that nanofluids are more impermeable cakes than the base fluid. Thermal conductivity was dramatically improved in the presence of both samples at 80 °C.